2010
DOI: 10.1177/1049909109358695
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Based Practices: Considerations for the Hospice Setting

Abstract: With tighter regulations and greater scrutiny of outcomes, hospice programs are being challenged to consider the implementation of Evidence-Based Practices (EBPs). This study reports the findings from interviews conducted with hospice directors and focus groups with the staff at eight experimental site hospice programs that occurred following the completion of a multifaceted translating research into practice (TRIP) intervention designed to promote the adoption of evidence-based pain management interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Additionally, engagement of physicians in the implementation process was difficult as noted by the ratings of nurses and other non‐physician hospice staff on the process evaluation questionnaire. Items related to physician involvement were all rated as least helpful in implementing the intervention and were also mentioned in the post‐intervention focus groups as barriers to implementation [15]. The issue of engaging physicians was also noted in the prior TRIP study conducted in the acute care setting [13].…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, engagement of physicians in the implementation process was difficult as noted by the ratings of nurses and other non‐physician hospice staff on the process evaluation questionnaire. Items related to physician involvement were all rated as least helpful in implementing the intervention and were also mentioned in the post‐intervention focus groups as barriers to implementation [15]. The issue of engaging physicians was also noted in the prior TRIP study conducted in the acute care setting [13].…”
Section: Discussionmentioning
confidence: 90%
“…The importance of guidelines and implementation strategies of these were highlighted (34). Staff culture is also described as an important factor for successful implementation of evidencebased medicine (EBM) into evidence-based practice (EBP) (35). Resistance to alter practice, conflict with competing priorities, lack of time and resources may be important barriers.…”
Section: Btp In the Out-patient Populationmentioning
confidence: 99%
“…Sanders et al (35) reported that agency culture might be an important barrier for implementing EBM into EBP. A standardized care pathway (SCP) might be an effective method to improve implementation (38,39) (40,41).…”
Section: Btp In the Out-patient Populationmentioning
confidence: 99%
“…23,31,32 Titler et al 23 utilized the model when developing strategies aimed at promoting EBP for management of acute hip pain in older patients with hip fracture. During the planning phase, each of the areas within the TRIP model was used to develop implementation strategies.…”
Section: Examples From Other Health-care Professionsmentioning
confidence: 99%
“…29 This model was selected as it has been shown to positively influence adoption of EBP when tested in other clinical environments. 23,[30][31][32] The model serves as a framework for developing strategies that promote implementation of EBP. It assumes that adoption of research is influenced by the characteristics of the EBP topic (type and strength of evidence; clinical relevance) and the manner in which it is communicated to users in a social system.…”
Section: Theoretical Frameworkmentioning
confidence: 99%